Gastrointestinal parasitic infections in cattle farms of Sikkim - PAL, PAPRI; CHATLOD, L R; AVASTHE, R K (The Indian Journal of Animal Sciences, 2015)
Of the total 303 faecal samples examined, 61 (20.13%) of them were found positive for different parasitic infections with eggs per gram of faeces (EPG) range of 100-700. The incidence was significantly lower in Government cattle farm (11.42%) than that of privately managed farms (22.75%). The most prevalent gastrointestinal helminth parasite eggs detected were strongyles (18.81%), Moniezia (11.22%), Ascaris (8.25%), Strongyloides (6.6%), coccidian oocyst (3.96%), Trichuris spp (2.31%), Nematodirus (1.66%) and amphistome (1.65%) in decreasing order. The prevalence of gastrointestinal parasitic infection was high in July (31.25%) and low in January (8.7%). Intensity of strongyle infection in terms of epg showed no variations when different ages, body conditions, breeds and lactation conditions were compared. The seasonal distribution of gastrointestinal parasitism indicated a higher percentage of infection during summer (29.11%) followed by spring (22.22%) and autumn (19.22%). The infection rate was significantly lower in winter (10.0%).